Fibroblasts Enhance Migration of Human Lung Cancer Cells in a Paper‐Based Coculture System. Issue 6 (30th December 2015) - Camci‐Unal, Gulden; Newsome, David; Eustace, Brenda K.; Whitesides, George M.
Abstract : A multilayered paper‐based platform is used to investigate the interactions between human lung tumor cells and fibroblasts that are isolated from primary patient tumor samples.